If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1225 + -12x = 0 Solving -1225 + -12x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '1225' to each side of the equation. -1225 + 1225 + -12x = 0 + 1225 Combine like terms: -1225 + 1225 = 0 0 + -12x = 0 + 1225 -12x = 0 + 1225 Combine like terms: 0 + 1225 = 1225 -12x = 1225 Divide each side by '-12'. x = -102.0833333 Simplifying x = -102.0833333
| -15+2x=21-x+4x | | 2x+x=160 | | 6(3x-2)=5(2x-2) | | x+(x+6)*2=60 | | -3(5k+8)=-24 | | -13=-h-(7) | | 17x+x+3x= | | 3(X+2)-(2X-7)=-(5X-1)-2(X+6) | | 6x=2y | | x(x+6)*2=60 | | 2y=-30 | | 10-3b=1-6b | | 5x-[2+3(1-x)]=2x+2(x-1) | | 5u^2+(-9u)+2=0 | | 7x^2+6x+4=0 | | 2(n+6)=-n | | .45+18n=441 | | 9h-3h=15 | | 2(3x+6)+4(4x+5)+3=22x+36 | | 4x^2+120=120 | | x^2+14x=1715 | | 3x=4+3x+x | | 5u^2-9u+2=0 | | 2*A+A^2=0.1 | | 9x=-10 | | 7N-10-9=-13 | | 4x+11=6x-1 | | 8n-10-12n=18 | | -4(-6x+7)=116 | | 249+0.99m=278 | | 10x^2+17x-63=0 | | 1.2x-3.6=2.4+1.8x |